Determinants of blockchain technology adoption among Zakat institutions in Malaysia: a proposed integrated model - Muhammad Ahmad, Shamsuddeen; Aminul Islam, MD; Mahadi, Nur Farhah (Istanbul Sabahattin Zaim University (IZU), 2020)
Blockchain is a cutting-edge technology that is capable of transforming and facilitating Zakat institutions to manage the Zakat proceeds and connect Zakat payers and recipients in a more effective and efficient way. However, despite many benefits that it can offer, the adoption rate is still very low especially in developing countries. While studies on blockchain have gained a relative pace over the recent years, the literature on this topic does not report adequate research cases on blockchain adoption behavior at the individual level. This study, therefore, aims to bridge this gap, notably by examining factors that influence blockchain adoption behavior among employees in Zakat institutions in Malaysia, Drawing on the emerging literature on blockchain, Zakat and network theory, as well as on Technology Acceptance Models (TAMs), we have developed an integrated model based on the Classical Unified Theory of Acceptance and Use of Technology (UTAUT2) and blockchain transparency. The research findings will be a platform to unravel the belief factors that influence the formation of attitude of the employees in Zakat institutions and their intention to adopt blockchain technology.